Mathematical Communication Ability from The Perspective of Math Anxiety in 10th Grade Student - Nurhasanah, Rizki Ahid; Waluya, St. Budi; Kharisudin, Iqbal (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe mathematical communication ability based on math anxiety in 10th grade student. This research method is descriptive qualitative. The research subjects were 36 students of class X MIPA 5 at SMA Negeri 1 Lasem in the academic year 2020/2021. The research data were collected through questionnaires, tests, interviews, and observations. The data analysis technique in this study was done through a process of reduction, categorization, and data validity. Based on the results of the study, there were students who had high, moderate, and low math anxiety. Mathematical communication ability of students with moderate and high math anxiety, there is the fact that there are those who master writing problems into mathematical modeling, solving mathematical problems, and making a settlement conclusion; some only mastered writing mathematical problems into mathematical modeling but did not master solving mathematical problems and making a settlement conclusion; there were also those who mastered writing mathematical problems into mathematical modeling and solving mathematical problems but did not master making a conclusion. Meanwhile, students' mathematical communication ability with low math anxiety mastered writing mathematical problems into mathematical modeling, solving mathematical problems, and making a settlement conclusion.